2010
DOI: 10.1159/000235919
|View full text |Cite
|
Sign up to set email alerts
|

Large Waist Circumference Is a Risk Factor for Reflux Esophagitis in Japanese Males

Abstract: Background/Aims: The prevalence of reflux esophagitis, which might lead to development of Barrett’s esophagus and esophageal adenocarcinoma, has been increasing. The aim of this study was to assess risk factors for reflux esophagitis. Methods: We conducted a cross-sectional study of 1,495 Japanese subjects undergoing health checkups (822 males and 673 females; median age 50 years) at a tertiary care center. Results: One hundred and twenty-seven subjects (8%) had reflux esophagitis and hiatal hernia was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 81 publications
2
16
0
Order By: Relevance
“…The prevalence of erosive GERD in Japanese was approximately 10 % [8][9][10] in studies involving 1000 or more subjects after 2008. Although only a small number of Fig.…”
Section: Summary Of Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of erosive GERD in Japanese was approximately 10 % [8][9][10] in studies involving 1000 or more subjects after 2008. Although only a small number of Fig.…”
Section: Summary Of Epidemiologymentioning
confidence: 99%
“…1 Algorithm for diagnosis and treatment of gastroesophageal reflux disease (GERD). a Diagnosis of GERD, b initial treatment for GERD, c long-term treatment strategy for GERD and therapeutic strategy for proton pump inhibitor (PPI)-resistant GERD reports described the endoscopic severity of erosive GERD, the frequency of severe erosive GERD (grade C or D of Los Angeles (LA) classification) cases was reported to be only 3 % [9], similar to that in previous reports, and the prevalence of GERD has been reported to reach an about two times higher level when heartburn symptoms are taken into account in the diagnosis [11].…”
Section: Summary Of Epidemiologymentioning
confidence: 99%
“…Observational studies from Asia have reported a consistent association between WC or VAT and RE [32,33]. Two studies of RE in a Japanese population showed that abdominal obesity may be an important risk factor for RE in males, but not in females [34,35], but another report did not show this association [36], which has led to some controversy about the association between obesity and RE. The present study clearly demonstrated that RE was an independent risk factor for ESBE, while obesity was not a risk factor for RE.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal obesity is a related prominent risk factor [49,50,51,52]. For example, the risk of EAC increased 3-fold for individuals with body mass indices >30 [50].…”
Section: Esophageal Adenocarcinomamentioning
confidence: 99%
“…In another study, abdominal obesity was found to be more important, as the risk of BE was more closely associated with waist-to-hip ratio than with body mass index [51]. A large waist circumference was also found to be a risk factor for reflux esophagitis [52]. Such types of obesity not only physically increase the episode of gastroesophageal reflux, but may also contribute to carcinogenesis by enhancing inflammation.…”
Section: Esophageal Adenocarcinomamentioning
confidence: 99%